Multiwavelength Transmission Spectroscopy Revisited for the Characterization of the Protein and Polystyrene Nanoparticle Mixtures. Issue 2 (February 2013) - Serebrennikova, Yulia M.; Roth, Alison; Huffman, Debra E.; Smith, Jennifer M.; Lindon, Jack N.; García-Rubio, Luis H.
Multiwavelength Transmission (MWT) UV-Vis-NIR spectroscopy, an effective technique often underutilized for the characterization of processes involving particulates, such as protein aggregation, is systematically explored using bovine serum albumin and a set of NIST-traceable particle size (PS) standards having certified particle diameters over the nominal size range of 30 to 100 nm. The PS standards are used as surrogates for protein aggregates and other contaminants such as oils and microbubbles. Therefore, the standards can be used to quantitatively modify the optical properties of protein solutions and thus observe the effect of the presence of aggregates and other particulates on their wavelength-dependent transmission spectra. The experimental results demonstrate that the changes induced in the optical density spectra of proteins due to the presence of PS particles are detectable and consistent with the expectations set by light scattering theory. It is demonstrated that the size and relative concentrations of the particle populations present in the protein samples can be quantified. Because of the considerable dynamic range of MWT UV-Vis-NIR spectroscopy for particle analysis and its real-time measurement capabilities, this type of spectroscopy can be effectively used for the characterization of protein aggregates and for the continuous real-time monitoring of aggregation processes and for the identification and quantification of contaminants in protein-based products.